Assymmetric effect exchange rate to Indonesian agriculture subsector - Sri Utami Lestari; Dedi Budiman Hakim; Tanti Novianti (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
This study explores the asymmetric effect on the rupiah exchange rate on every subsector agriculture export in Indonesia during 2006-2020. The non-linear ARDL method is used in this study to analyze the asymmetric relationship between exchange rate and export. NARDL method includes short-run and long-run coefficient estimates and embraces the asymmetric effect. The previous studies generally used the linear models on the aggregated data and ignored the differences in each export of the agricultural sub-sector, then they offered ambiguous results. The latest studies have preferred to use the method of NARDL on the agricultural sector in general data. Instead of using agricultural export data for each subsector, this paper considers subsector export data of agriculture. The estimated NARDL results indicate an asymmetric effect of the rupiah exchange rate on exports of the agricultural sub-sector in the long run. In general, there is no asymmetric effect in the short run. Generally, depreciation and appreciation of the Rupiah have a negative effect on exports of the agricultural sub-sector in the long run. However, rupiah appreciation positively impacts lag 2, and depreciation caused a different effect on each sub-sector. The NARDL results suggest that positive movements have lesser impacts than those of negative movements in the exchange rate on the agriculture sector both in the short and long run